2006
DOI: 10.1017/s0952523806230190
|View full text |Cite
|
Sign up to set email alerts
|

Postreceptoral adaptation abnormalities in early age-related maculopathy

Abstract: Age-related maculopathy (ARM) has become the major cause of blindness in the Western World. Currently its pathogenesis and primary site of functional damage is not fully understood but ischemia is believed to play a major role. Early detection and precise monitoring of progression of ARM are main goals of current research due to lack of sufficient treatment options, especially in the dry, atrophic form of this disease. We applied the multifocal electroretinogram (mfERG) that can detect any local functional def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Analysis of the global flash mfERG revealed a significant reduction of its early waveform component (DR) in the early ARM group compared to the age‐similar healthy group (Figure 1B). We inferred that both waveform components reflected post‐receptoral functional deficits located within the ON and OFF bipolar cells and the outer and inner plexiform layer in early ARM 69 …”
Section: Functional Measures Of Ischaemiamentioning
confidence: 96%
See 2 more Smart Citations
“…Analysis of the global flash mfERG revealed a significant reduction of its early waveform component (DR) in the early ARM group compared to the age‐similar healthy group (Figure 1B). We inferred that both waveform components reflected post‐receptoral functional deficits located within the ON and OFF bipolar cells and the outer and inner plexiform layer in early ARM 69 …”
Section: Functional Measures Of Ischaemiamentioning
confidence: 96%
“…Psychophysical function tests have not yet separated primary receptoral and post‐receptoral deficits 67,68 . We have applied an electrophysiological technique for measuring post‐receptoral responses by using the multifocal electroretinogram (mfERG, Veris Science 5.1.5X, EDI Inc, Redwood City, CA, USA) 11,69 . In its conventional, fast flicker application, the mfERG measures cone‐mediated ON and OFF bipolar cells but also inner retinal cell contributions 70 .…”
Section: Functional Measures Of Ischaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported the efficacy of the mfERG in the assessment of ARMD [6,19,20,29,33,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Multifocal Ergmentioning
confidence: 99%
“…The slow flash mfERG is another paradigm that has been subtracted from the conventional fast flicker mfERG to assess non-linear adaptive components within the retina in ARM [48]. Interestingly, neither conventional mfERG nor slow flash mfERGs discriminated between the ARM group and age-similar controls.…”
Section: Multifocal Ergmentioning
confidence: 99%